Chromatin-dependent allosteric regulation of DNMT3A activity by MeCP2 - Rajavelu, Arumugam (Nucleic Acids Res, 2018)
Despite their central importance in mammalian development, the mechanisms that regulate the DNA methylation machinery and thereby the generation of genomic methylation patterns are still poorly understood. Here, we identify the 5mC-binding protein MeCP2 as a direct and strong interactor of DNA methyltransferase 3 (DNMT3) proteins. We mapped the interaction interface to the transcriptional repression domain of MeCP2 and the ADD domain of DNMT3A and find that binding of MeCP2 strongly inhibits the activity of DNMT3A in vitro. This effect was reinforced by cellular studies where a global reduction of DNA methylation levels was observed after overexpression of MeCP2 in human cells. By engineering conformationally locked DNMT3A variants as novel tools to study the allosteric regulation of this enzyme, we show that MeCP2 stabilizes the closed, autoinhibitory conformation of DNMT3A. Interestingly, the interaction with MeCP2 and its resulting inhibition were relieved by the binding of K4 unmodified histone H3 N-terminal tail to the DNMT3A–ADD domain. Taken together, our data indicate that the localization and activity of DNMT3A are under the combined control of MeCP2 and H3 tail modifications where, depending on the modification status of the H3 tail at the binding sites, MeCP2 can act as either a repressor or activator of DNA methylation.